An efficient method to separate silicon from high-silicon aluminum alloy melts by electromagnetic directional solidification. (1st June 2018) - He, Yunfei; Ma, Wenhui; Lv, Guoqiang; Zhang, Yufeng; Lei, Yun; Yang, Xi
Abstract: In electromagnetic directional solidification, the silicon phase cannot always be completely separated, resulting in considerable waste of power and silicon. This study investigated the electromagnetic separation of silicon by using electromagnetic induction-heated directional solidification furnaces at varying frequencies. Two frequencies were applied to separate silicon from aluminum–silicon melts. Numerical simulation results indicated that a low frequency (3 kHz) could substantially enhance the separation of silicon from aluminum–silicon melts under an alternating electromagnetic field, which could increase the speed of the melts to 0.92 cm/s. Experimental results showed that separation efficiency could exceed 85% at a pulling rate of 10 μm/s when a furnace at a frequency of 3 kHz was used. This method can potentially meet the requirements of manufacturing low-cost solar cells for industrial use. Highlights: An efficient separation method was carried out. Low frequency electromagnetic field can make strong melt flow for separation. Separation efficiency reach 85% after electromagnetic directional solidification. After EM-DS with 3 kHz, only two parts in the sample.